Projet pilote de nettoyage des fonds marins du canal d’Adjim: retrait des filets de pêche perdus (Association pour la Sauvegarde de l’île de Djerba, 2014)
le projet vise à : - Rétablir le cycle de ponte et de reproduction des poissons de façon à revitaliser les ressources halieutiques. - Contribuer à la réapparition des espèces devenues de plus en plus rares - Sensibiliser et éduquer les pêcheurs et les exploitants de la mer à la protection des ressources halieutiques et à la renonciation aux pratiques de pêche interdites.
Keywords: Pêche -- Djerba

Project on Regional Development Planning of the Southern Region in the Republic of Tunisia : Final Report Executive Summary (Japan International Cooperation Agency, 2015)

تقرير مفوض الأمم المتحدة السامي لحقوق الإنسان عن حالة حقوق الإنسان في ليبيا وعن الاحتياجات ذات الصلة من الدعم التقني وبناء القدرات (مجلس حقوق الإنسان, 2015)
يقدم هذا التقرير عن حالة حقوق الإنسان في ليبيا وعن الاحتياجات ذات الصلة من الدعم التقني وبناء القدرات عملاً بقرار مجلس حقوق الإنسان 25/37 المؤرخ 28 آذار/ مارس 2014. وتواجه ليبيا أسوأ أزمة سياسية مرت بها مع تصاعد حدة العنف منذ اندلاع النزاع المسلح في عام 2011. فهناك برلمانان وحكومتان يدعيان الشرعية في الوقت الذي تمارس فيه مجموعات مسلحة قوية سيطرتها الفعلية على أرض الواقع، وترتكب انتهاكات القانون الدولي لحقوق الإنسان والقانون الإنساني الدولي في ظل إفلات الفاعلين من العقاب. ولا يزال النظام القضائي عرضة للهجمات بل إنه لم يعد يعمل في أجزاء من البلد. وفي هذا السياق، تعطلت المساعدة التقنية بشكل كبير. غير أن بعض مؤسسات الدولة ومنظمات المجتمع المدني لا تزال تعمل بدرجات متفاوتة وتحتاج إلى مساعدة. ويقدم التقرير لمحة عامة عن حالة حقوق الإنسان في ليبيا وعلى المساعدة التقنية المقدمة لدعم المؤسسات الرئيسية والجهات الفاعلة في المجتمع المدني. ويتضمن التقرير توصيات لمعالجة مسألة حماية المدنيين، وتحسين إقامة العدل ودعم الإصلاح القانوني، والعدالة الانتقالية، والمؤسسات الوطنية.
Keywords: Vie politique -- Djebel Nefousa

تقرير حول محاكمة 37 عضو في نظام القذافي (2012/630 قضية) (بعثة الأمم المتحدة للدعم في ليبيا, 2017)
Keywords: Vie politique -- Djebel Nefousa

Oman: National Challenges and Regional Issues in the Post-Sultan Era - Dazi-Héni, Fatiha (Note de recherche, 2017)
This report outlines the main national and international issues at stake with the potential succession of Sultan Qaboos, whose health began to decline in 2014. He will be difficult to replace due to his status as the Father of the Nation who brought the country out of the feudal era. He modernized the state and gave it a diplomatic role as a mediator which has become extremely valuable in a region constantly on the brink of tensions and conflicts. In the short term, his successor will be faced with a difficult task due to falling oil prices affecting the economy. In the medium term, the challenge will be to revive a social contract that is running out of steam. However Oman’s diplomatic role as a mediator in the region and an intermediary between Washington and Tehran, along with its strategic position at a crossroads on the Silk Road play in the country’s favour in getting regional and global players to support the post-Qaboos Sultanate
Keywords: Politique étrangère -- Oman -- 1970-2020

Oman: défis intérieurs et enjeux régionaux dans la perspective de l’après-sultan - Dazi-Héni, Fatiha (Note de recherche, 2017)
Cette note expose les principaux enjeux intérieurs et extérieurs dans le contexte d’une succession possible du sultan Qabous, dont l’état de santé s’est aggravé en 2014. Son remplacement sera difficile à assurer en raison du statut de père de la Nation dont jouit le sultan, qui a sorti son pays de l’ère féodale. Il l’a modernisé et l’a doté d’une diplomatie de médiation devenue incontournable dans une région propice aux tensions et conflits. À court terme, la tâche du successeur s’avèrera la plus ardue, en raison de la baisse des prix du pétrole qui affecte la situation économique. À moyen terme, l’enjeu sera de renouveler un pacte social à bout de souffle. Cependant, le rôle de médiation de la diplomatie omanaise dans la région et de facilitateur entre Washington et Téhéran, ajouté à sa position stratégique, au carrefour de la Route de la soie, plaident pour qu’acteurs régionaux et globaux soutiennent le sultanat de l’après-Qabous.
Keywords: Vie politique -- Oman -- 1970-2020

Can Oman’s Stability Outlive Sultan Qaboos? - Cafiero, Giorgio; Karasik, Theodore (MEI Policy Focus, 2016)
Keywords: Vie politique -- Oman -- 1970-2020

Compte-rendu de la visite de la délégation officielle de Djerba en Allemagne - Jebali, Besma; Laghouane, Schéhérazade; Hajjam, Lassaad; Jrad, Houcine; Ben Jemaa, Mohamed; Elouati, Mehdi; Zerria, Ezzedine (Délégation de Djerba, 2018)

Saranno Rispettati Come per il Passato. Italian Colonial Policy Towards Libyan Religious Endowments - Gazzini, Claudia (EUI Working Paper, 2010)

Etude sur les « Organisations et initiatives en faveur de la participation des jeunes dans la commune de Jerba Midoune » - Ben Abdallah, Sénim; Saadi, Lotfi (Comun, 2013)
Keywords: Communes -- Djerba

Oman: A State Elaborating a Nation - Peterson, John E. (Commentary, 2019)
Keywords: Vie politique -- Oman -- 1970-2020

Les spécificités architecturales du sud tunisien : répertoire et recommandations - Gdoura, Mahmoud; Trabelsi, Raja (Direction de l'urbanisme, 2016)
Keywords: Ammi Yathi, mosquée (Fahmine, Djerba); Architecture -- Djerba; Monuments -- Djerba

Simmering Unrest and Succession Challenges in Oman - Valeri, Marc (Carnegie Endowment for International Peace, 2015)
Keywords: Vie politique -- Oman -- 1970-2020

Oman’s mediatory efforts in regional crises - Valeri, Marc (Noref Expert Analysis, 2014)
Oman’s role in facilitating the conclusion of the Iran-P5+1 nuclear deal in November 2013 and its announcement a few weeks later that it would not join a proposed Gulf union can be understood within a recent history of conciliatory efforts intended to promote negotiated solutions to regional crises. Oman has always perceived political instability in the Gulf and West Asia as a factor threatening the country’s own internal stability. This perception of political vulnerability also explains the sultanate’s determination to prevent foreign actors from interfering in its internal affairs. The price for this independent foreign policy towards its neighbours has been the country’s unquestioned political and military dependence on Britain and the U.S. Given Oman’s strategic importance to the security of the entire Gulf, controlling as it does the Strait of Hormuz, through which approximately one-third of the world’s seaborne trade in crude petroleum passed in 2013, Britain and the U.S. have shared Muscat’s aversion for any disruption of its internal status quo and wish to prevent any contamination of Omani territory by unwanted foreign influence.
Keywords: Vie politique -- Oman -- 1970-2020

Oman's Quiet Diplomacy - Jones, Jeremy (NUPI Papier, 2014)
Hemmelige samtaler mellom Iran og USA startet i Oman i mars 2013. Disse beredte grunnen for atomvåpenavtalen «Joint Plan of Action» som ble inngått 24. november i fjor mellom stormaktene og Iran. Gjennom å føre en utenrikspolitikk rettet mot å vedlikeholde gode relasjoner med sine naboer, har Oman lenge stått for et stille diplomati i høflighetens og diskresjonens ånd. Andre karakteristiske trekk ved Omans utenrikspolitikk er toleranse, dypt rotfestet pragmatisme og en aversjon mot sekterisk og ideologisk konflikt. Og i motsetning til enkelte andre arabiske regjeringer, er Oman ikke redd for Iran. Denne artikkelen er skrevet av Jeremy Jones, som driver et strategisk analysebyrå i Oxford, Storbritannia. Han er også Senior Associate Member på Oxford Centre for Islamic Studies, Senior Fellow for internasjonale relasjoner ved National Council for US Arab Relations i Washington DC og Research fellow på Dubai School of Government. Han er forfatter (sammen med Nicholas Ridout) av boken Oman, Culture and Diplomacy, utgitt av Edinburgh University Press (2012).

Democracy in Slow Motion: Oman Goes to the Polls - Carpenter, J Scott; Henderson, Simon (PolicyWatch, 2017)
Keywords: Vie politique -- Oman -- 1970-2020

Report of the Special Rapporteur on the situation of human rights and fundamental freedoms of indigenous people - Stavenhagen, Rodolfo (Nations Unies, 2017)
Libyan Arab Jamahiriya : Letter regarding allegation in relation to the Berber community § 298-302
Keywords: Vie politique -- Djebel Nefousa

Les Berbères en Tunisie (Tamazgha, 2018)
Keywords: Berbérisme -- Tunisie

Etude d'impact sur l'environnement (EIE) du projet de réalisation de la station de dessalement d'eau de mer à Djerba (Ingénierie de l'Hydraulique, de l'Equipement et de l'Environnement, 2015)

Armed groups in Libya after the elections - what can be expected? - Pusztai, Wolfgang (Istituto per gli Studi di Politica Internazionale Ente del Terzo Settore, 2014)
Keywords: Vie politique -- Djebel Nefousa

إحياء الذكرى 34 للإغلان عن تأسيس حركة الاتجاه الإسلامي / حركة النهضة 6/6/1981 - 6/6/2015 - الودرني, صالح بن عمارة; كسكاس, عاشور يوسف (المكتب المحلي لحركة النهضة بآجيم جربة, 2015)
Keywords: Biographies -- Djerba -- 20e siècle

The Jewish Community of Djerba, Tunisia and the event of La Ghriba - Miller, Eva (The University of the South International and Global Studies Religion, 2016)
Keywords: Judaïsme -- Djerba

The Importance of the Image of a Destination in the Choice and Intention of Revisiting: The Case of Island of Djerba. - Abdellatif, Tarek; Ksouri, Rabii; Hayoun, Souheila; Storai, Christophe (Social Science Research Network, 2014)
The image of a destination is a key element to attract tourists. This image is based on the perceptions of individuals about the destination, which determines their touristic behavior and, consequently, their choice of destination (Woodside and Lysonski 1989; Echtner and Ritchie, 1993). Thus, the objective of this research is to analyze the strategic dimension of the image of a destination as a strategic management tool in order to understand the conductive elements to maintain and / or revive touristic streams to the destination. For this goal, authors have conducted a study including an analysis of the image of the island of Djerba with Jewish tourists. The results will be discussed later on strategic options of what could a positive image represent in order to conceive a successful attraction strategy which arouses the intention of revisiting within tourists.
Keywords: Tourisme -- Djerba

Gestion optimisée des déchets en Méditerranée : Diagnostic de la gestion des déchets hôteliers au niveau de Djerba. Résultats et recommandations (SBA, 2010)
Keywords: Crises environnementales -- Djerba

Djerba : une leçon d'art et d'architecture - Tiouajni, Mahfoudh (2010)
Mon rapport de voyage d'étude à Djerba
Keywords: Architecture -- Djerba

Vers un schéma directeur de développement intégré à l’île de Djerba - Ayari, Ghana (Association des Architectes de Djerba, 2017)
Keywords: Architecture -- Djerba

Negotiating the Future, observations and visions of urban phenomena in Djerba - Salheen, Mohamed (IUSD Ain Shams University, 2013)
Keywords: Architecture -- Djerba

Towards a Sustainable Development of the Coastal Zones in Tunisia – Case Study of Lella Hadhria - Stokman, Antje; Jörg, Johannes; Caballero, Alicia Ruiz (IUSD-Lab, 2014)

Profil de durabilité dans quelques destinations touristiques méditerranéennes. Synthèse: la destination de Djerba en Tunisie. A partir de l’étude de cas réalisée par Jean Mohamed Mehdi CHAPOUTOT - Bourse, Loïc (PNUE, 2011)
Keywords: Tourisme -- Djerba

Profil de durabilité dans quelques destinations touristiques méditerranéennes. La destination Jerba en Tunisie - Chapoutot, Jean Mohamed Mehdi (PNUE, 2011)
Keywords: Tourisme -- Djerba

Étude d’impact sur l’environnement (EIE) du projet de realisation de la station de dessalement d’eau de mer à Djerba - Bencharrada, Rafik (Sonede, 2015)

Nappe phréatique de l’île de Jerba: Aspects hydrogéologiques et mobilisation des ressources - Yahyaoui, Houcine (Commissariat régional de l’Agriculture, 2012)
Keywords: Géologie -- Djerba

Les oiseaux nicheurs sur les îles et îlots de l’archipel de Jerba - Ouni, Ridha (Note naturaliste Initiative PIM, 2015)
Keywords: Faune -- Djerba